2023
DOI: 10.3389/feart.2022.1030224
|View full text |Cite
|
Sign up to set email alerts
|

Charcoal in Kunlun Mountains loess: Implications for environment change and human activity during the middle Holocene

Abstract: Loess sediment charcoal records are used in paleoecological analyses to reconstruct fire history and human activities. The Tarim Basin is bordered to the south by the Kunlun Mountains, where eolian silt or loess is extensive and has continued to be deposited in modern times. In this study, we conducted multiple analyses of a 720 cm–thick loess section (KLA) at 3,516 m elevation in the Kunlun Mountains to reconstruct the middle Holocene vegetation history in northern China. Our palynological, charcoal, and grai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Progress in speleothem and tree-ring studies over recent years has revealed new insights into the climate in order to interpret the region's historical human-environment interactions [10,11]. An increasing number of local paleoenvironmental reconstructions are becoming available to enable the better understanding of historical human activity patterns [12][13][14]. Archaeological and historical research has established a framework for the history of human activity in the Tarim Basin.…”
Section: Introductionmentioning
confidence: 99%
“…Progress in speleothem and tree-ring studies over recent years has revealed new insights into the climate in order to interpret the region's historical human-environment interactions [10,11]. An increasing number of local paleoenvironmental reconstructions are becoming available to enable the better understanding of historical human activity patterns [12][13][14]. Archaeological and historical research has established a framework for the history of human activity in the Tarim Basin.…”
Section: Introductionmentioning
confidence: 99%